Malawi : Fifth and Sixth Reviews Under the Extended Credit Facility Arrangement, Request for Waivers for Non-Observance of Performance Criteria, Extension of the Arrangement, Modification of Performance Criterion, and Rephasing of Disbursements. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Malawi's Fifth and Sixth Reviews Under the Extended Credit Facility (ECF) Arrangement, Request for Waivers for Non-observance of Performance Criteria (PCs), Extension of the Arrangement, Modification of PCs, and Rephasing of Disbursements. Program implementation was uneven given external financing shortfalls with several PCs not being observed. Three out of seven PCs for the fifth review were not met, including the continuous PC on the contracting of nonconcessional external loans. The new authorities are firmly committed to the core policies and objectives of the original ECF-supported program. Program discussions focused on key policy actions to address these challenges and bring the program back on track.